2019
DOI: 10.1021/acsaelm.9b00078
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility MoS2 Directly Grown on Polymer Substrate with Kinetics-Controlled Metal–Organic Chemical Vapor Deposition

Abstract: Batch growth of high-mobility (μFE > 10 cm2V–1s–1) molybdenum disulfide (MoS2) films can be achieved by means of the chemical vapor deposition (CVD) method at high temperatures (>500 °C) on rigid substrates. Although high-temperature growth guarantees film quality, time- and cost-consuming transfer processes are required to fabricate flexible devices. In contrast, low-temperature approaches (<250 °C) for direct growth on polymer substrates have thus far achieved film growth with limited spatial homogeneity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…27 Regardless of the precursors used, the growth often results in a polycrystalline film with domain sizes in the order of nanometers. 25 , 28 , 29 Recently, MOCVD growths of MoS 2 with domain sizes larger than 10 μm have been reported. However, they involve long processing times (∼26 h per monolayer) 23 or require the substrates to be pre-exposed to halides, 25 , 30 which form the sodium/potassium metal oxide layer below the TMD monolayer, as a byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…27 Regardless of the precursors used, the growth often results in a polycrystalline film with domain sizes in the order of nanometers. 25 , 28 , 29 Recently, MOCVD growths of MoS 2 with domain sizes larger than 10 μm have been reported. However, they involve long processing times (∼26 h per monolayer) 23 or require the substrates to be pre-exposed to halides, 25 , 30 which form the sodium/potassium metal oxide layer below the TMD monolayer, as a byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…The common precursors of the transition metals (Mo(CO) 6 and W(CO) 6 , WCl 6 ) and the chalcogens (H 2 S, H 2 Se, and (CH 3 ) 2 Se) for growing TMDs have high ambient vapor pressures and can dissociate below 400°C. [58][59][60] The substrate temperature needs to be high enough (i.e., >700°C) [56] to overcome the kinetic limitations, including the balance between the adsorption and desorption and surface diffusion of adatoms to obtain electronic grade materials. [61,62] On the other hand, it can also grow 2D TMDs in polycrystalline forms at 450°C and is suitable for the back-end-of-line (BEOL) integration in Si technology thanks to the high reactivity of metal-organic precursors.…”
Section: Thin-film Techniques For the Compositional Engineering Of 2d Tmdsmentioning
confidence: 99%
“…[61] At low growth temperatures, the growth shifts from a mass-transfer limited process to a surface-reaction controlled process [62] with higher attachment rates and lower surface adatom mobility yielding smaller, less geometrically "sharp" grains. [61] Efforts in obtaining higher-quality TMD films at lower growth temperatures include growth promoters, [60,113] substrate engineering, [114] or careful precursor ratio tuning. [68,73,115] Solution-based methods have also been explored to produce 2D TMDs at low processing temperatures.…”
Section: Low-temperature Effortsmentioning
confidence: 99%
“…Under this strategy, Mun et al reported MoS 2 with a grain size of 100–200 nm grown for 8 h at 250 °C and a moderate pressure of 30 torr. Here, the growth temperature is more than 250 °C lower than that of typical CVD (>500 °C) 75. The second strategy is based on the fact that the chemical reaction proceeds in a direction maintaining its equilibrium.…”
Section: Transition Metal Dichalcogenides Tftsmentioning
confidence: 99%